Immersion and distancing during assimilation of problematic experiences in a good-outcome case of emotion-focused therapy - Barbosa, Eunice (2016)
Some studies have suggested that a decrease in immersion (egocentric perspective on personal experiences) and an increase in distancing (observer perspective on personal experiences) are associated with the resolution of clinical problems and positive outcome in psychotherapy for depression. To help clarify how this change in perspectives relates to clinical change, the present study compared changes in immersion and distancing across therapy with progress in one client's assimilation of her problematic experiences.